Maxims of university leadership - Sahol Hamid Abu Bakar (Penerbitan UiTM Press, 2012)
This book is must read for leaders or for those who aspire to become leaders at institutions of higher education. This book shares the author's many years of higer education leadership experience, woven together with a unique blend of anecdotes and powerful kernels of leadership wisdom, tinged with a local flavour. The maxims outlined in this book provide rich insights into the leadership issues at higher education while also providing tried and true details of the actions required in handling these issues. The maxims also provide a wide range of perspectives that encompasses the management, associates in leadership, staff, students and stakeholders.